Mémoire du travail et des expositions professionnelles aux cancérogènes - Béatrice Leconte; Annie Thébaud-Mony (Perspectives Interdisciplinaires sur le Travail et la Santé)
According to official estimates, in the year 2000, approximately 32 million European workers (in Europe 15) were exposed to carcinogens. Since 2002, considering the disease as a "sentinel-event" for understanding the work activities that expose workers to carcinogens, the GISCOP93 research group has been carrying out an ongoing survey on patients with cancer in Seine-Saint-Denis (France). Based on the patients’ narratives and on the expertise of exposure hazard specialists, an analysis and classification of the exposed working activities was carried out to build a new database of work activities in the presence of carcinogenic products/processes. The aim of this article is to present this database in relation to some other sources of information on occupational exposure to carcinogens, already available on-line, while showing the contribution of a knowledge-gathering method based on the workers’ experience and statements.